Deficient IL-12p70 secretion by dendritic cells based on IL12B promoter genotype - Müller-Berghaus, Jan; Paschen, Annette; Nguyen, Xuan Phuc; Klüter, Harald; Schadendorf, Dirk (Genes and immunity, 2004)
Interleukin-12 (IL-12), a heterodimeric cytokine, is important in the generation of a Th1-biased immune response. Several polymorphisms have been described in IL12B, the gene encoding the p40 subunit of IL-12. A bi-allelic polymorphism within the IL12B promoter region has been reported to show association with diseases as diverse as severe childhood asthma and fatal cerebral malaria. In order to define the molecular basis for these disease associations, we investigated the secretion of IL-12 by human monocyte-derived dendritic cells. Homozygotes for the IL12B promoter polymorphism showed a 10-fold difference in median p70 secretion in response to CD40 ligation. Remarkably, this difference resulted from the inability of most allele 1 homozygotes to secrete heterodimeric IL-12. In contrast, most of the donors homozygous for allele 2 had detectable secretion. These findings are important for the understanding of the highly complex regulation of IL-12 secretion, and its consequent impact on disease susceptibility, in humans.
Gesehen am 10.12.2020